Patient Satisfaction: Assessment Analysis of Service Quality and Trust In Health Facilities - Ulfa Hrp, Fitri Aidani (Pena Cendekia Insani, 2024)
Puskesmas plays an important role in providing the best service to people who want to get health services. However, in the field it is still a classic problem that one of the problems is the aspect of service to patients who are considered less than satisfied. Of course, this must receive attention as an evaluation material regarding the quality of service that needs to be carried out so that patients will again have confidence and be willing to visit the health center, considering that the health center is the first level health facility in the national health insurance program, even resulting in patient satisfaction. The aim of this paper is to analyze the influence of service quality and trust on patient satisfaction at the outpatient installation of Puskesmas X in Labuhan Batu. This research is an analytical observational type using a cross-sectional approach. The sample size was 100 patients seeking treatment at the outpatient installation of Puskesmas X in Labuhan Batu. The sampling technique was carried out using systematic random sampling. Data was obtained directly through patients' perceptions of the perceived quality of service, their trust in the facilities and services received, including the satisfaction felt by patients through questionnaire instruments. The data obtained was then analyzed using binary logistic regression. The results showed that all patients (82%) stated that the overall dimensions of service quality were good, and almost all patients (80%) expressed confidence and almost all respondents (82%) stated that they were satisfied with the service at the Outpatient Installation of Puskesmas X in Labuhan Batu . Then service quality has a significant effect on patient satisfaction (p-value = 0.042) and trust has a significant effect on patient satisfaction (p-value = 0.010). The research conclusion shows that service quality and trust can influence patient satisfaction.